2021
DOI: 10.21037/atm-21-340
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of spinal cord injury subtypes using weighted gene co-expression network analysis

Abstract: Background: Spinal cord injury (SCI) has an immediate and devastating impact on the control over various movements and sensations. However, no effective therapies for SCI currently exist.Methods: To identify and analyze SCI subtypes, we obtained the expression profile data of the 1,057 genes (889 intersection genes) in GSE45550 using weighted gene co-expression network analysis (WGCNA), and 14 co-expression gene modules were identified. Next, we filtered out the network degree top 10 (degree >80) genes, consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…GO and KEGG pathway analysis showed that most of these genes are related to cell cycle and DNA replication, and participate in cell proliferation. The hub genes obtained by cytohub screening are Cdk1, Ccna2, Ccnb2, Ccnb1, Kif20a, Top2a, Aurka, Ns5atp9, Ube2c, Birc5, which are partially consistent with previous studies [52][53][54] . Cyclin-dependent kinase 1(Cdk1) is a member of serine/threonine kinase expressed in splinter cell, which is involved in the transition between G2 phase and mitosis.…”
Section: Discussionsupporting
confidence: 91%
“…GO and KEGG pathway analysis showed that most of these genes are related to cell cycle and DNA replication, and participate in cell proliferation. The hub genes obtained by cytohub screening are Cdk1, Ccna2, Ccnb2, Ccnb1, Kif20a, Top2a, Aurka, Ns5atp9, Ube2c, Birc5, which are partially consistent with previous studies [52][53][54] . Cyclin-dependent kinase 1(Cdk1) is a member of serine/threonine kinase expressed in splinter cell, which is involved in the transition between G2 phase and mitosis.…”
Section: Discussionsupporting
confidence: 91%
“…In line with our study, Q. Chen et al. ( 2021 ) also used WGCNA to detect gene expression in SCI and found that six genes may serve as a potential prognostic target for the diagnosis and treatment of SCI.…”
Section: Discussionsupporting
confidence: 89%
“…Chen et al (2021) also used WGCNA to detect gene expression in SCI and found that six genes may serve as a potential prognostic target for the diagnosis and treatment of SCI.However, the limitation of our study was that the limited data published in the open dataset and the incomprehensive clinicopathological features analyzed may lead to potential statistical bias. Therefore, a more comprehensive study should be conducted in the future to identify more biomarkers for SCI treatment.In conclusion, we identified DEGs, enriched signaling pathways, and hub genes in the young and aged SCI groups.…”
mentioning
confidence: 96%
“…In the interictal PBMC samples, 31 miRNAs were DE compared to healthy controls, including hsa-miR-5189-3p, hsa-miR-96-5p, hsa-miR-3613-5p, hsa-miR-99a-3p, and hsa-miR-542-3p. hsa-miR-5189-3p closely correlates with spinal cord injury and is part of a set of transcripts proposed to have a role in classifying the disease [85]. The miR-96 and its miR-183 family have been observed to be regulated in diverse regions of the somatosensory nociceptive pathway in different chronic pain conditions in rodents [86].…”
Section: Discussionmentioning
confidence: 99%